Meralgia Paresthetica After Spine Surgery on the Jackson Table. Issue 2 (March 2018) - Agarwal, Nitin; Mistry, Jaydev B.; Khandge, Preeya V.; Hansberry, David R.; Goldstein, Ira M.
Abstract : Meralgia paresthetica is a non–life-threatening neurological disorder characterized by numbness, tingling, and burning pain over the anterolateral thigh due to impingement of the lateral femoral cutaneous nerve. This disorder has been seen in patients with diabetes mellitus and obesity, but has also been observed in patients after procedures such as posterior spine surgery, iliac crest bone grafts, lumbar disk surgery, hernia repair, appendectomies, and pelvic osteotomies that ultimately lead to compression or damage to the lateral femoral cutaneous nerve. Overall, permanent sequelae of meralgia paresthetica are rare, however, some cases do require intervention.